Yeast protein expression profile during acetic acid-induced apoptosis indicates causal involvement of the TOR pathway - Almeida, Bruno Miguel Barroso Rodrigues (2009)
Although acetic acid has been shown to induce apoptosis in yeast, the exact apoptotic mechanisms remain unknown. Here, we studied the effects of acetic acid treatment on yeast cells by 2-DE, revealing alterations in the levels of proteins directly or indirectly linked with the target of rapamycin (TOR) pathway: amino-acid biosynthesis, transcription/translation machinery, carbohydrate metabolism, nucleotide biosynthesis, stress response, protein turnover and cell cycle. The increased levels of proteins involved in amino-acid biosynthesis presented a counteracting response to a severe intracellular amino-acid starvation induced by acetic acid. Deletion of GCN4 and GCN2 encoding key players of general amino-acid control (GAAC) system caused a higher resistance to acetic acid indicating an involvement of Gcn4p/Gcn2p in the apoptotic signaling. Involvement of the TOR pathway in acetic acid-induced apoptosis was also reflected by the higher survival rates associated to a terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL)-negative phenotype and lower reactive oxygen species levels of Deltator1 cells. In addition, deletion mutants for several downstream mediators of the TOR pathway revealed that apoptotic signaling involves the phosphatases Pph21p and Pph22p but not Sit4p. Altogether, our results indicate that GAAC and TOR pathways (Tor1p) are involved in the signaling of acetic acid-induced apoptosis.